2012
DOI: 10.1016/j.aim.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

On a conjecture of Anosov

Abstract: In this paper, we prove that for every bumpy Finsler n-sphere (S n , F ) with reversibility λ and flag curvature K satisfying λ λ+1 2 < K ≤ 1, there exist 2[ n+1 2 ] prime closed geodesics. This gives a confirmed answer to a conjecture of D. V. Anosov [Ano] in 1974 for a generic case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 27 publications
1
41
0
1
Order By: Relevance
“…In this setting, the right analog of the dynamical convexity condition is the requirement that µ − ≥ n − 1 for all closed Reeb orbits of α. For the unit sphere bundle of a Riemannian or Finsler metric, this requirement is satisfied, for instance, when the metric meets certain curvature pinching conditions; see, e.g., [AM14,DLW,HP,Ra04,Wa12]. Along the lines of Theorem 1.5, we have the following result.…”
Section: Introduction and Main Resultsmentioning
confidence: 90%
“…In this setting, the right analog of the dynamical convexity condition is the requirement that µ − ≥ n − 1 for all closed Reeb orbits of α. For the unit sphere bundle of a Riemannian or Finsler metric, this requirement is satisfied, for instance, when the metric meets certain curvature pinching conditions; see, e.g., [AM14,DLW,HP,Ra04,Wa12]. Along the lines of Theorem 1.5, we have the following result.…”
Section: Introduction and Main Resultsmentioning
confidence: 90%
“…The same author proved in [36] that for every Finsler n-dimensional sphere S n for n ≥ with reversibility λ and flag curvature K satisfying (λ/( + λ)) < K ≤ , either there exist infinitely many prime closed geodesics or there exist [n/ ] − closed geodesics possessing irrational mean indices. Furthermore, assuming that the metric F is bumpy, he showed in [35] that there exist [(n + )/ ] closed geodesics on (S n , F). Also, in [35], he showed that for every bumpy Finsler metric F on S n satisfying ( / )(λ/( + λ)) < K ≤ , there exist two prime elliptic closed geodesics provided the number of closed geodesics on (S n , F) is finite.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Furthermore, assuming that the metric F is bumpy, he showed in [35] that there exist [(n + )/ ] closed geodesics on (S n , F). Also, in [35], he showed that for every bumpy Finsler metric F on S n satisfying ( / )(λ/( + λ)) < K ≤ , there exist two prime elliptic closed geodesics provided the number of closed geodesics on (S n , F) is finite.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…There are many works using Morse theory and index theory to study the closed geodesics and Anosov Conjecture in Finsler geometry, assuming a pinch condition for the flag curvature, non-degenerating property for all closed geodesics, or using the speciality of low dimensions. See for example [7] [11] [12] [13] [15] [18] [19]. From the geometrical point of view, it was much later that people noticed that Katok metrics are Randers metrics on spheres with constant flag curvature [16].…”
Section: Introductionmentioning
confidence: 99%